Selective estrogen receptor modulators regulate reactive microglia after penetrating brain injury - Barreto, George E.; Santos-Galindo, Maria; Garcia-Segura, Luis Miguel (Frontiers in Aging Neuroscience, 2014)
Following brain injury, microglia assume a reactive-like state and secrete pro-inflammatory molecules that can potentiate damage. A therapeutic strategy that may limit microgliosis is of potential interest. In this context, selective estrogen receptor modulators, such as raloxifene and tamoxifen, are known to reduce microglia activation induced by neuroinflammatory stimuli in young animals. In the present study, we have assessed whether raloxifene and tamoxifen are able to affect microglia activation after brain injury in young and aged animals in time points relevant to clinics, which is hours after brain trauma. Volume fraction of MHC-II+ microglia was estimated according to the point-counting method of Weibel within a distance of 350 μm from the lateral border of the wound, and cellular morphology was measured by fractal analysis. Two groups of animals were studied: 1) young rats, ovariectomized at 2 months of age; and 2) aged rats, ovariectomized at 18 months of age. Fifteen days after ovariectomy animals received a stab wound brain injury and the treatment with estrogenic compounds. Our findings indicate that raloxifene and tamoxifen reduced microglia activation in both young and aged animals. Although the volume fraction of reactive microglia was found lower in aged animals, this was accompanied by important changes in cell morphology, where aged microglia assume a bushier and hyperplasic aspect when compared to young microglia. These data suggest that early regulation of microglia activation provides a mechanism by which SERMs may exert a neuroprotective effect in the setting of a brain trauma.